2010
DOI: 10.1055/s-0030-1247598
|View full text |Cite
|
Sign up to set email alerts
|

Packed Red Blood Cell Transfusion Increases Regional Cerebral and Splanchnic Tissue Oxygen Saturation in Anemic Symptomatic Preterm Infants

Abstract: Preterm infants often receive multiple packed red blood cell (PRBC) transfusions that are intended to improve tissue oxygen levels. Near-infrared spectroscopy (NIRS) monitors regional cerebral tissue oxygen saturation (CrSO(2)) and splanchnic tissue oxygen saturation (SrSO(2)). Before such technology can be employed in neonatal transfusion management, it must first be established that transfusions result in an increase in tissue oxygen saturation. This prospective, observational study used NIRS to determine if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 27 publications
9
94
3
3
Order By: Relevance
“…We have shown that blood transfusion in preterm infants increased cerebral tissue oxygenation index (cTOI) as well as cerebral tissue haemoglobin index (cTHI) during the first [8][9][10]38 . In these studies preterm infants of 5 to 93 days of age with a wide range of pre-transfusion Hb were clubbed together as a single group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that blood transfusion in preterm infants increased cerebral tissue oxygenation index (cTOI) as well as cerebral tissue haemoglobin index (cTHI) during the first [8][9][10]38 . In these studies preterm infants of 5 to 93 days of age with a wide range of pre-transfusion Hb were clubbed together as a single group.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for transfusion in preterm infants remain controversial and has led to several randomised controlled trials using liberal and restrictive thresholds for blood transfusion with conflicting reports on neurological outcomes [5][6][7] . Whether these thresholds were not optimal or whether haemoglobin concentration in the blood does not correlate with tissue oxygenation measurements [8][9][10] remains to be answered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used in preterm infants for various healthcare conditions such as respiratory distress syndrome, 7 red blood cell transfusion, 8 desaturations, 9 indomethacin therapy 10,11 or ligation of a patent ductus arteriosus 12,13 and during the critical first days of life. [14][15][16][17] Major determinants of the regional tissue oxygen saturation are changes in SpO 2 , regional perfusion, regional blood volume and metabolic rate of oxygen utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we have limited ways to monitor tissue oxygenation and measure the effect of transfusion. New techniques, under evaluation, may ultimately provide better information on the effect of transfusion [3][4][5]. Near infrared spectroscopy has been applied to monitor cerebral circulation (INVOS system: http://www.…”
Section: Clinical Studies Of O 2 Delivery By Red Cellsmentioning
confidence: 99%